2012
DOI: 10.4236/jmmce.2012.116041
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Corrosion-Erosion Behaviour of Carbide based Thermal Spray Coatings

Abstract: Thermal spraying has emerged as a suitable and effective surface engineering technology and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…The protection of pipeline steel by the use of inorganic coatings has been reported by many researchers [19][20][21][22]. Fan et al [19,20] investigated the protection of pipeline steels enamel coatings, while Chatha et al [21] studied the effect of the Cr 3 C 2 -NiCr coating layer on the corrosion protection of T91 boiler steel under different types of environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protection of pipeline steel by the use of inorganic coatings has been reported by many researchers [19][20][21][22]. Fan et al [19,20] investigated the protection of pipeline steels enamel coatings, while Chatha et al [21] studied the effect of the Cr 3 C 2 -NiCr coating layer on the corrosion protection of T91 boiler steel under different types of environments.…”
Section: Introductionmentioning
confidence: 99%
“…The protection of pipeline steel by the use of inorganic coatings has been reported by many researchers [19][20][21][22]. Fan et al [19,20] investigated the protection of pipeline steels enamel coatings, while Chatha et al [21] studied the effect of the Cr 3 C 2 -NiCr coating layer on the corrosion protection of T91 boiler steel under different types of environments. The authors [21] claimed that this coating offers a high melting point and maintains high hardness, strength and wear resistance up to a maximum operating temperature of 900 • C. Tillmann et al [22] also claimed that the Cr 3 C 2 -NiCr coating features a very low porosity, low oxidization and low carbide decomposition or carbide-matrix dissolution, which leads to increasing hardness and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It was The carbides in the metallic matrix can individually act as cathodes in the microgalvanic cells [13]. It has been shown that the connection of the carbide (Cr 3 C 2 as cathode) to the metal matrix (NiCr as anode) forms a microgalvanic cell that increases the corrosion rate of the NiCr binder, and inherently destroys the coatings [14,15]. The galvanic cell leads to a severe attack of the NiCr binder once the coating is penetrated, and an electric contact between NiCr and Cr 3 C 2 is formed in an electrically conducting corrosive liquid [16].…”
Section: Introductionmentioning
confidence: 99%
“…While theoretically, coatings may be employed in a variety of ways to modify, hinder or thwart the corrosion reaction [2]. Various conventional methods such as carburizing, nitriding, electroplating are used over a century to protect tools; however, the development of the hard protective coatings in the narrower sense, started in the sixties with the discovery of chemical vapour deposition and physical vapour deposition tech-niques [3]. In recent times, modern deposition techniques such as thermal spray and laser cladding have become more popular and give large throughput in shortest possible time [4].…”
Section: Introductionmentioning
confidence: 99%